Technical Efficiency of Maize Production in Nigeria: Parametric and Non-Parametric Approach - Hassan, Yusha’u; Abdullah, Amin Mahir bin; Ismail , Mohd Mansor; Mohamed, Zainalabidin (Asian Journal of Agriculture and Rural Development, 2014)
The study was carried out to provide empirical evidence on technical efficiency of maize production in Nigeria using parametric and non-parametric approaches. The study employed annual secondary data on maize production in Nigeria from 1971 to 2010.Stochastic Frontier Analysis (SFA) and Data Envelopment Analysis (DEA) were used to estimate the technical efficiency of maize production. The results revealed that, the mean technical efficiency scores were 64.1%, 77.8% and 87.7% for technical efficiency under stochastic frontier analysis, technical efficiency of DEA constant return to scale and technical efficiency of DEA variable return to scale assumptions, respectively. These showed that the efficiency scores obtained from DEA are higher than those obtained from SFA. The results implied that, the country can expand its scope of output production by 35.5%, 22.2% and 12.3% for technical efficiency under stochastic frontier analysis, data envelopment analysis constant return to scale and variable return to scale, respectively. It is concluded that under the two methods used farmers can still expand their scope of output production through appropriate combination and use of production inputs at the given technology.